2020
DOI: 10.1017/jfm.2020.428
|View full text |Cite
|
Sign up to set email alerts
|

Non-Newtonian effects on the slip and mobility of a self-propelling active particle

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Similar conclusions appear to apply qualitatively to autophoretic Janus particle [118,119]. In that case, the type of swimmer (pusher vs. puller) is determined by the sign of the local phoretic mobility and the ratio between active and inert regions.…”
Section: Squirmer Modelsupporting
confidence: 63%
“…Similar conclusions appear to apply qualitatively to autophoretic Janus particle [118,119]. In that case, the type of swimmer (pusher vs. puller) is determined by the sign of the local phoretic mobility and the ratio between active and inert regions.…”
Section: Squirmer Modelsupporting
confidence: 63%
“…Recent exceptions include the experimental works [315][316][317] which have provided important insights into the dynamics of active particles in viscoelastic media (so far mainly at the single particle level). In addition, the very recent theoretical work [318] has shown that viscoelastic effects can significantly modify the slip velocity on the active surface of the particles, which should have profound consequences not only for the single particle behavior but also for the (phoretic) cross-interactions of these particles.…”
Section: Memory and Solute Advection Effectsmentioning
confidence: 99%
“…Very recently, for active droplets in a viscoelastic media, Dwivedi et al demonstrated a Peclet-induced transition in the swimming mode and also deformation in their shapes . For phoretic colloids, numerous theoretical and computational studies have attempted to understand the behavior of self-propelled colloids in complex media. So far, light-activated JCs have been chiefly used to study the dynamics of active JCs in viscoelastic media experimentally. ,,, Gomez-Solano et al demonstrated that the bulk viscoelastic stresses decouple the translational and rotational dynamics of the active JC . Narinder et al showed that increasing the propulsion force resulted in persistent cycloid trajectories .…”
Section: Introductionmentioning
confidence: 99%